2021
DOI: 10.5802/crchim.90
|View full text |Cite
|
Sign up to set email alerts
|

Optimal parameters and structural composition of bio-oil and biochar from intermediate pyrolysis of red algal biomass

Abstract: Sustainable Biomass Resources for Environmental, Agronomic, Biomaterials and Energy Applications 2 / Ressources de biomasse durables pour des applications environnementales, agronomiques, de biomatériaux et énergétiques 2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…The most developed processes at a commercial scale are first-generation biofuels production and the heat/electricity co-generation through combustion technique. However, the other thermochemical conversion techniques, namely pyrolysis and gasification are experiencing a great development with various applications offering direct production of heat and/or electricity, biofuels and high valueadded chemicals [1,[9][10][11][12][13][14]. The pyrolysis process is a thermochemical conversion technique leading to the formation of three fractions: bio-oil (liquid), bio-char (solid) and syngas.…”
Section: Introductionmentioning
confidence: 99%
“…The most developed processes at a commercial scale are first-generation biofuels production and the heat/electricity co-generation through combustion technique. However, the other thermochemical conversion techniques, namely pyrolysis and gasification are experiencing a great development with various applications offering direct production of heat and/or electricity, biofuels and high valueadded chemicals [1,[9][10][11][12][13][14]. The pyrolysis process is a thermochemical conversion technique leading to the formation of three fractions: bio-oil (liquid), bio-char (solid) and syngas.…”
Section: Introductionmentioning
confidence: 99%
“…Another study of intermediate pyrolysis on red algal biomass revealed the maximum yield at 50 • C/min and 450 • C for bio-oil. The bio-oil, biochar, and gas yields were 45.02 wt.%, 33.34 wt.%, and 21.64 wt.%, respectively [5]. Intermediate pyrolysis has an excellent product distribution of biochar, bio-oil, and syngas and is more flexible for treating waste biomass [6].…”
Section: Introductionmentioning
confidence: 99%